2012
DOI: 10.3109/14756366.2011.633907
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, 2D-NMR and molecular modelling studies of pentacycloundecane lactam-peptides and peptoids as potential HIV-1 wild type C-SA protease inhibitors

Abstract: In this study, eight non-natural peptides and peptoids incorporating the pentacycloundecane (PCU) lactam were designed and synthesized as potential inhibitors of the wild type C-SA HIV-protease. Five of these inhibitors gave IC(50) values ranging from 0.5 up to 0.75 µM against the resistance-prone wild type C-South African HIV-protease. NMR EASY-ROESY studies enabled us to describe the secondary structure of three of these compounds in solution. The 3D structures of the selected cage peptides were also modelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…As the X‐ray crystal structure of C‐SA HIV PR was not yet resolved, we previously reported the use of a computationally generated enzyme model. The modeling scenario and validation of the created C‐SA HIV PR model have been reported in our previous work . Even though the X‐ray crystal structure of the C‐SA HIV PR (PDB code: 3U71) was recently published , we believe that the use of the modeled enzyme system would still be more appropriate for several reasons.…”
Section: Methodsmentioning
confidence: 95%
“…As the X‐ray crystal structure of C‐SA HIV PR was not yet resolved, we previously reported the use of a computationally generated enzyme model. The modeling scenario and validation of the created C‐SA HIV PR model have been reported in our previous work . Even though the X‐ray crystal structure of the C‐SA HIV PR (PDB code: 3U71) was recently published , we believe that the use of the modeled enzyme system would still be more appropriate for several reasons.…”
Section: Methodsmentioning
confidence: 95%
“…The Leap module of amber12 package was used to add missing protons to the protein. Particularly, the protonation state of the catalytic Asp25 residue has been examined in our previous work and other studies, according to our previous investigations, showed that there is no significant difference between the binding free energy results for the monoprotonated and unprotonated states; therefore, the Asp25 residues in this study were left in the unprotonated state . The Amber force field for bioorganic systems (ff03.r1) was used in describing the parameters of the protein, while the inhibitors were described by GAFF parameters as implemented on amber12 .…”
Section: Methodsmentioning
confidence: 99%
“…Even though this subtype comprises 70% of the global HIV infection to date, very little experimental and computational work on the C‐SA protease has been reported. Publications investigating the impact of active site mutations on binding energies in the C‐SA protease and the inhibition thereof by pentacycloundecane lactam peptides and peptoids make up a substantial proportion of literature on C‐SA protease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Until late 2012, the X‐ray crystal structure of the C‐SA PR was unavailable, limiting information on how drugs interact with this enzyme. A computational model for the C‐SA PR based on its protein sequence was developed [Mosebi et al., ] and used in previous studies [Makatini et al., 2011a, b, ; Honarparvar et al., ; Karpoormath et al., ]. Recently, the first X‐ray crystal structure of C‐SA HIV PR was reported [Naicker et al., ], allowing comparison of the unique structural and dynamic features of the C‐SA PR enzyme with subtype B.…”
Section: Introductionmentioning
confidence: 99%